(untitled) (Experimental biology, 2025)
The study examines the negative impact of emissions from a phosphorus plant located near the city of Taraz in the Zhambyl region on the ecological functions of soils, including the activity of soil fauna as a bioindicator, compared to soils in the region 10 km away from the plant. Soil fauna plays an important role in the formation of soil properties, such as its fertility, humification and mineralization of plant residues, as well as changes in the salt regime and soil reaction, which improves its physicochemical characteristics. In addition, the activity of soil animals contributes to the formation of a granular soil structure, which makes it more resistant to environmental influences. The study examined the species Isotoma, Folsomia, Onychinus, Hypogastrura, represented in the Collembola (long-legged insects), as part of the soil fauna. It was revealed that the Onychinus species is most often found in the sandstone layer at depths ...